Body size and testicular traits of tropically-adapted bucks raised under extensive husbandry in Ethiopia - Mekasha, Yoseph; Tegegne, Azage; Abera, A.; Rodríguez Martinez, H. (Wiley, 2008)
Five tropically adapted buck breeds extensively managed in Ethiopia were studied to determine possible effects of breed and age on body size and testicular traits. In all, 177 bucks were selected following stratified random sampling, and evaluated in three age groups: <14 months (young), 14-19.5 months (intermediate) and 19.6-24 months (old). The breeds studied were Arsi-Bale (AB; N = 35), Central Highlands (CH; N = 33), Afar (N = 35), Boran (N = 36) and Woito-Guji (WG; N = 38). In all the three age groups, Boran and CH bucks were the heaviest (p < 0.05), Afar were the lightest, and AB and WG were in between. The highest body weight (BW) was achieved in the intermediate age group for Afar, but in the oldest age group for the other breeds. In the youngest age group, scrotal circumference (SC) was the widest (p < 0.05) for Boran and CH and the narrowest for Afar, AB and WG, while in the intermediate and the oldest age groups, Boran showed the widest SC. Boran, WG and CH had higher (p < 0.05) testicular weight (TW) than Afar and AB in the youngest age group. Boran retained the highest (p < 0.05) TW in the intermediate and the oldest age groups, while in the oldest age group WG and AB medium TW and Afar had the lowest TW. However, Afar had the highest TW expressed as percentage of BW. SC was well correlated with TW (p < 0.001; r = 0.74) and BW (p < 0.001; r = 0.61), indicating a linear, positive association between BW and TW (p < 0.001; r = 0.51). In conclusion, body size and testicular traits of Ethiopian bucks under an extensive management system are influenced differently by breed and age group.